Pessoas LGBTQIAP+ e o enfrentamento da homofobia: histórias de vida e superação na vida de mulheres lésbicas - Souza, Nataly Barbosa de (Brasil, 2024)
Lesbian, Gays, Bisexuals, Transsexuals, Transgenders, Transvestites, Queer, Intersex, Asexual and Pansexuals (LGBTQIAP+) are often targets of intolerance and violence by people who refuse to recognize human plurality. In their own way, these people cope with such setbacks.Thus, the objective of this study is to understand the process of facing and overcoming homophobic situations on the experiences of lesbian women in Manaus, from the perspective of Martin Heidegger's phenomenology The research was carried out using a qualitative approach, with a descriptive and exploratory characteristic. The method used was phenomenological-psychological and data was obtained through audio-recorded phenomenological interviews that started from a guiding question and analyzed from the perspective of Martin Heidegger's Phenomenology. 5 lesbian women collaborated in the research. Three Thematic Categories were created, with subcategories: 1. Sexuality: temporalizing the trajectory; 2. The search for acceptance: the self-view and the gaze of others; 3. The various selves: self-care, self-understanding, self-recognition. At the end of the study, the diversity of their experiences related to confronting homophobia was learned, moving through themes such as discoveries, self-knowledge, violence and self-understanding, themes that contribute to to reflect on reality and to develop practical proposals with these women.